2016
DOI: 10.1016/j.transproceed.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Good Outcomes in Kidney Transplantation With Deceased Donor With Acute Kidney Injury: Donor's Age and Not Acute Kidney Injury Predicts Graft Function

Abstract: Kidney transplantation of organs from deceased donors with AKI showed greater DGF but good outcomes. Donor age was the only characteristic that correlated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Several studies have observed that organs from donors with AKI are associated with a higher incidence of DGF, but all these studies focused on adult donors. Si Nga et al explored the relationship between DGF and donor age (mean age >50 years) among adult donors with AKI and found that one additional year of donor age increased the risk of DGF by 1.08 times ( P = 0.01); however, AKI stages could not predict the risk of DGF . By contrast, we noted an increased incidence of DGF in higher AKI stages, and the multivariate regression analysis of adult groups confirmed that the higher was the AKI stage, the higher was the risk of DGF.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have observed that organs from donors with AKI are associated with a higher incidence of DGF, but all these studies focused on adult donors. Si Nga et al explored the relationship between DGF and donor age (mean age >50 years) among adult donors with AKI and found that one additional year of donor age increased the risk of DGF by 1.08 times ( P = 0.01); however, AKI stages could not predict the risk of DGF . By contrast, we noted an increased incidence of DGF in higher AKI stages, and the multivariate regression analysis of adult groups confirmed that the higher was the AKI stage, the higher was the risk of DGF.…”
Section: Discussionsupporting
confidence: 57%
“…5,8 This characteristic is also important to consider in cases of renal donation whose donor is in AKI, the age of the donor, rather than the final creatinine value has a greater association with outcome and worsening renal function in 6 months. 9 The histological assessment of the AKI kidneys is fundamental, as it shows their viability before implantation. The absence or discrete histological lesions correlate with good graft survival in one year, favoring the use of the organ offered; while the presence of moderate to severe lesions correlates with poor graft survival, making transplantation unwise.…”
Section: Discussionmentioning
confidence: 99%
“…All patients reported in this series had DGF, as expected, since the percentage of graft delay in renal donors with AKI is high. 6,7,8,9 The main risk factor and probable etiological factor for DGF is the KDIGO III AKI diagnosis validity prior to donation. Other risk factors include the long dialysis time prior to transplantation in the first case and the 25-hour CID in the third case.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that AKI in donor kidneys has an impact on acute rejection episodes in recipients [17]. Many studies have presented similar survival rates for kidneys from AKI and non-AKI groups, despite using different definitions of AKI [18]. Zuckerman et al.…”
Section: Discussionmentioning
confidence: 99%